Factors Limiting the Full-scale Adoption of Process and Product Innovation in the Nigerian Construction Industry - Emmanuel Chidiebere Eze; Onyinye SOFOLAHAN; Adesoji Anthony ADEGBOYEGA; Kenneth John SAIDU (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- The aim of this study is to assess the factors limiting the full-scale adoption of process and product innovation by construction organizations in Nigeria with a view to suggesting probable ways of eliminating them Design/Methodology- The study adopted a questionnaire survey approach in which data were collected from the participants using simple random sampling techniques in the study area. Frequency, percentage, mean item score, and Independent sample T-test was used to analyze the gathered data. Findings- It was found that poor funding, poor support and commitment from management, fragmented nature of the construction business, poor coordination and communication among project participants, lack of qualified and experienced staff and the unwillingness of clients to pay for innovative ideas are the factors limiting innovations in construction. Practical Implications- The outcome of this study will give the management of construction-based organizations an insight into the major limiting factors of innovation, so that appropriate strategies for overcoming them could be developed at the conception stage of construction projects.